Craft Revival and Self-Directed Learning Among Young Women During the Pandemic - Pearson, Sarah (The Canadian Art Teacher / Enseigner les arts au Canada)

(untitled) (Canadian Society for Education through Art / Société canadienne d’éducation par l’art, 2024)
This article aims to summarize a grounded theory inquiry to examine renewed interests in craft practices. Through remote interviews with female participants in their early twenties, and several rounds of data coding three emergent themes were identified: moving beyond traditional learning trajectories, art as function, and implications for sustainability. Investigating what motivates these women to engage creatively, and how they gained knowledge about their chosen mode of creative production, this inquiry reveals the self-directed nature of craft learning. Self-directed learning (SDL) is becoming more prevalent due to the increasing availability of resources and is therefore recognized for its validity as a contemporary learning approach. Especially relevant is the redemptive and autonomous qualities of both craft and self-directed learning in the context of the Covid-19 pandemic. This investigation cracks the surface of how craft-making and learning have been impacted by the pandemic, justifying the importance of independence, accessibility, and co-construction in teaching and learning.